PENGARUH PH PADA MEDIA AIR RAWA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) - Khoirun Nisa; Marsi .; Mirna Fitrani (Universitas Sriwijaya, 2013)
ABSTRACT Snakehead fish is one of swamp fish species that has not been successfully cultivated intensively, therefore it is necessary to do a particular effort for rearing snakehead fish. Rearing of fry snakehead fish in the swamp water media by modifiying pH is expected to be able to support the survival rate and growth.The research uses CDR with 5 treatments and 3 replications. Modification of water pH will be done by adding HCl or NaOH. Increasing or decreasing pH will be conducted continuosly for 30 days. The result of this research showed that continues modification of rearing media pH is very significantly affected survival rate of fry snakehead fish with P3 (decreasing from pH 5.75 to pH 5.00) as the best treatment. This treatment gave survival rate of 67.90% and weight biomass of 9.8982 grams Keywords : Fry snakehead fish, pH, swamp water, survival rate and growth Â